Pengembangan E-Modul Menggunakan Flip PDF Professional pada Materi Fungi Kelas X SMA - Anggi Aprilia; Yudiyanto Yudiyanto; Nasrul Hakim (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
The production of e-modules utilizing Flip PDF Professional on Fungi material is inspired by the use of subpar technology and the usage of printed media in learning (powerpoint). Students struggle to comprehend the information. As a result, the goal of this research is to create an e-module using Flip PDF Professional. The ADDIE development model phases are used in this study to apply the R&D (Research and Development) development approach. Material expert validators deemed the outcomes of e-module product validation utilizing Flip PDF Professional